Heat management strategies in elite rugby sevens - Fenemor, S. P. (University of Waikato, 2022)
The purpose of this thesis was to develop and implement heat management strategies for international elite men`s and women`s rugby sevens teams competing in hot and humid conditions. The first three of six experimental chapters aimed to characterise the physiological, perceptual, and performance perturbations that undertaking rugby sevens specific exercise in hot and humid conditions involves. The following three experimental chapters built upon these characterisations by investigating practical, training-integrated interventions, designed to alleviate the stressors that collectively impair performance.